Unifying physics of accelerators, lasers and plasma - Seryi A. Andrei (Boca Raton, Taylor & Francis, 2016)
Unifying Physics of Accelerators, Lasers and Plasma introduces the physics of accelerators, lasers and plasma in tandem with the industrial methodology of inventiveness, a technique that teaches that similar problems and solutions appear again and again in seemingly dissimilar disciplines. This unique approach builds bridges and enhances connections between the three aforementioned areas of physics that are essential for developing the next generation of accelerators.